The Effects of Photostimulation on Stem Cell Growth and Differentiation. - Wilner, Joshua Irving. (Tufts Archival Research Center, 2005)
Photostimulation deals with the use of light to activate molecules, pathways, and functions within cells. Photostimulation techniques can be applied to tissue engineering in vitro to reduce the field's dependency on chemical growth factors by using light to control stem cell proliferation and differentiation. Researchers have previously shown that photostimulation positively affects cell proliferation, extracellular matrix composition and organization, and the rate of healing (de Souza 2005; Medrado 2008; Kushibiki 2009). However, the effects of various wavelengths of visible light on stem cell growth and differentiation have not been previously studied. Human mesenchymal stem cells (hMSCs) were photostimulated with LEDs at wavelengths of 455, 470, 528, 617, and 656nm. Experiments analyzing hMSCs' proliferation and bone differentiation were performed. It was determined that blue light at 455 and 470nm had an inhibitory effect on cell proliferation and differentiation. Red light at 656nm had positive effects on hMSC differentiation shown by increased alkaline phosphatase (ALP) and calcium production after two weeks. It was concluded that blue light's higher energy inhibited the cells' metabolic activity, while red light's lower energy enhanced bone differentiation. These positive results suggest that photostimulation can improve the mechanical properties and functionality of bone tissue engineering models.